Islamic Business Ethics As A Basic of Policies Facing The Impact of Covid-19 Pandemics - Ratna Sofiana; Dini Amalia Rizky (Universitas Wahid Hasyim, 2021)
Morals are very important in every action in the life of a Muslim, including in his business activities. In a difficult or happy situation a Muslim must continue to prioritize in order to create the benefit of the whole community. In difficult circumstances such as in early 2020 where the world and Indonesia were shocked by the emergence of the COVID-19 virus which disrupted the health and economy of the country. At such times it is important to review the establishment of policies that can provide welfare for all levels of society both from the government or business actors in accordance with applicable norms and culture. This research . This research was conducted with a literature review method using analysis of secondary data. The results of this study indicate that some requirements that are in accordance with Islamic business ethics must be considered by the government and business actors, namely establishing clear and transparent information platforms, setting standards on business activities and products that are in accordance with health regulations to control the needs of community products, and making public educative. Keywords: pandemic, company policy, regulation, welfare.